Media coverage of human rights in the USA and UK: the violations still will not be televised (or published) - Brandle, Shawna M. (Human rights review, 2018)
This article analyzes American television and American and British print news coverage of human rights using a combination of manual and machine coding. The data reveal that television and print news cover very few human rights stories, that these stories are mostly international and not domestic, that even when human rights are covered, they are not covered in detail, and that human rights issues are more likely to be covered when they are not framed as human rights. This suggests that human rights is simply not a frame that journalists employ and provides support for government-leading-media theories of newsworthiness.